Patient-reported quality of life progression in men with prostate cancer following primary cryotherapy, cyberknife, or active holistic surveillance. Issue 3 (September 2018) - Werneburg, Glenn; Kongnyuy, Michael; Halpern, Daniel; Salcedo, Jose; Kosinski, Kaitlin; Haas, Jonathan; Schiff, Jeffrey; Corcoran, Anthony; Katz, Aaron
Abstract Background Technological advancements have led to the success of minimally invasive treatment modalities for prostate cancer such as CyberKnife and Cryotherapy. Here, we investigate patient-reported urinary function, bowel habits, and sexual function in patients following CyberKnife (CK) or Cryotherapy treatment, and compare them with active holistic surveillance (AHS) patients. Methods An IRB-approved institutional database was retrospectively reviewed for patients who underwent CK, Cryotherapy, or AHS. Quality of life (QoL) survey responses were collected every three months and the mean function scores were analyzed in yearly intervals over the 4 years post-treatment. Results 279 patients (767 survey sets) were included in the study. There was no difference among groups in urinary function scores. The CyberKnife group had significantly lower bowel habit scores in the early years following treatment (year 2 mean difference: −5.4, P < 0.01) but returned to AHS level scores by year 4. Cryotherapy patients exhibited initially lower, but not statistically significant, bowel function scores, which then improved and approached those of AHS. Both CyberKnife (year 1 mean difference: −26.7, P < 0.001) and Cryotherapy groups (−35.4, P < 0.001) had early lower sexual function scores relative to AHS, but then gradually improved and were not significantly different from AHS by the third year post-treatment. A history of hormonal therapy was associated with a lower sexual function scores relative to those patients who did not receive hormones in both CyberKnife (−18.45, P < 0.01) and Cryotherapy patients (−14.6, P < 0.05). Conclusions After initial lower bowel habits and sexual function scores, CyberKnife or Cryotherapy-treated patients had no significant difference in QoL relative to AHS patients. These results highlight the benefit of CyberKnife and Cryotherapy in the management of organ-confined prostate cancer.